2018
DOI: 10.3892/ol.2018.8151
|View full text |Cite
|
Sign up to set email alerts
|

The family of apoptosis-stimulating proteins of p53 is dysregulated in colorectal cancer patients

Abstract: The apoptosis-stimulating protein of p53 (ASPP) family is a newly identified family protein including ASPP1, ASPP2 and inhibitor of ASPP (iASPP), by which the tumor protein 53 (TP53)-mediated apoptotic process is selectively regulated. Downregulation of ASPP1/ASPP2 and upregulation of iASPP were revealed to be associated with a poor prognosis and metastasis in several types of cancer. However, to the best of our knowledge, the expression of ASPP in colorectal cancer (CRC) has not previously been investigated. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Tumor apoptosis is a hallmark in the pathogenesis and treatment for human cancer patients ( 33 35 ). Li et al ( 36 ) indicated that growth arrest and apoptosis of the human hepatocellular carcinoma cell line BEL-7402 could be induced by melittin by up-regulation of Fas expression.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor apoptosis is a hallmark in the pathogenesis and treatment for human cancer patients ( 33 35 ). Li et al ( 36 ) indicated that growth arrest and apoptosis of the human hepatocellular carcinoma cell line BEL-7402 could be induced by melittin by up-regulation of Fas expression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is growing evidence that overexpression, rather than mutation, of iASPP conveys its oncogenic properties. In addition to our previous characterization in p53 wild-type breast cancer (32), elevated iASPP levels have recently been reported in multiple human cancers, including bladder cancer (63), non-small-cell lung cancer (64), ovarian clear cell carcinoma (65), colorectal cancer (66), and particularly in acute leukemia where p53 mutations are relatively rare (67, 68).…”
Section: Discussionmentioning
confidence: 67%
“…The role of ASPP1 in cancer has been reported in several studies 21,22,25,[42][43][44] . However, the relationship between ASPP1 and metastasis has never been reported in CRC.…”
Section: Discussionmentioning
confidence: 99%
“…High ASPP2/low iASPP expression in a number of human cancers has been evaluated and found to correlate with higher survival rates, improved curative effect and better prognosis [17][18][19][20][21][22] . Meanwhile, ASPP1 has been found to be downregulated in a variety of human cancers including acute lymphoblastic leukemia, breast cancer, hepatitis B virus-positive hepatocellular carcinoma, clear cell renal cell carcinoma and colorectal cancer (CRC) [21][22][23][24][25] . Previously, we have demonstrated that ASPP2 downregulation can promote invasion and migration by controlling β-catenin-dependent regulation of ZEB1 26 ; however, the mechanisms underlying ASPP1's functions in CRC remain unclear.…”
Section: Introductionmentioning
confidence: 99%